Morphogenesis of extra-embryonic tissues directs the remodelling of the mouse embryo at implantation - Neophytos Christodoulou (Nature Portfolio, 2019)
How the shape of the pre-implantation murine embryo changes dramatically upon implantation is unclear. Here, the authors use live imaging with a cdx2-GFP reporter line in combination with loss of function experiments to demonstrate that FGF signalling mediated trophectoderm morphogenesis orchestrates this process.